Dynamical analysis of a Crowley-Martin Eco-epidemiological model with impact of fear, prey refuge and harvesting - Arumugam Divya; Muthurathinam Sivabalan; Mehmet Yavuz; Anbulinga Ashwin; Manickasundaram Siva Pradeep (Jambura Journal of Biomathematics (JJBM), 2025)
We develop an eco-epidemiological model that includes three species comprising a food web: vulnerable prey, diseased prey, and predator species that transmit disease to their prey. A population of prey consists of two subpopulations: healthy prey (susceptible prey), which follow the logistic law and are capable of reproducing, and diseased prey, which are destroyed by predation or die before reproducing. A predator devour vulnerable and infected prey in various proportions in a Crowley-Martin type of interaction.  In the Crowley-Martin functional response, there is interdependence among predators, regardless of whether a particular predator is actively seeking prey or interacting with prey at any given time. In Holling-type II interactions, vulnerable prey is consumed by infected prey.